Perbandingan Efektivitas Transmisi Moneter Kredit Perbankan Konvensional dan Syariah di Indonesia serta Hubungannya dengan Pergerakan Suku Bunga - Cupian, Cupian; Ahmadsyah, Ibnu; Noven, Sarah Annisa (ITB AAS INDONESIA Surakarta, 2025)
Monetary transmission is aimed to stabilize prices and to increase output in the long run. This study compares the effectiveness of transmission of conventional and Islamic banking loans in Indonesia to the consumer price index (CPI) and industrial production index (IPI), to find out which transmission is more effective and the direction of its influence, and to see the role of credit interest rates or its equivalent to the amount of credit or financing as the most important variable in transmission, to test the authenticity of Islamic banks in relation to interest rates. Secondary data used is sourced from Bank Indonesia, Federal Reserve Economic Data, OJK, BPS, and BIS, by using the quantitative Vector Error Correction Model (VECM) method with the period of January 2009 – December 2017. The results of the study show that the transmission of conventional bank credit is more effective in influencing the monetary end target. Meanwhile, Islamic banks are actually more responsive than conventional banks towards increasing interest rates or their equivalent in the decision to grant financing, so it can be concluded that Islamic banking faces a higher risk of fluctuations in interest rates.